2016
DOI: 10.24843/jbiounud.2016.v20.i01.p04
|View full text |Cite
|
Sign up to set email alerts
|

PERAKITAN IKAN LELE (Clarias sp.) TRANSGENIK DENGAN TEKNIK ELEKTROPORASI SPERMA

Abstract: Aplikasi teknologi transfer gen melalui perantaraan sperma dimungkinkan untuk memperbaiki kualitas genetik ikan. Keberhasilan transfer gen hormon pertumbuhan (Growth Hormone =GH) ikan budidaya melalui elektroporasi sperma dapat menghasilkan ikan transgenik. Pada penelitian ini dilakukan transfer konstruksi vektor ekspresi gen GH lele dumbo (pTarget-CMV-CgGH) ke sperma lele dumbo (strain mutiara) menggunakan kejut listrik 125 Vcm-1 dengan jumlah pulsa 3 dan 5 serta 50 Vcm-1 dengan jumlah pulsa 3 dan 5. Konsentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Recently, transgenesis development for aquatic animal is better to be transferred using electroporation method, because electroporation considered more suitable for the aquaculture and does not require special skills [8]. That is also seen in the efficacy of succesful gene transfer using sperm elctroporation method that has been reported to have higher efficiency compared with microinjection method, as shown in ayu fish (Plecogosus altivelis) the successful of gene transfer is 55%, in zebrafish and moad loach are 80%, in indian gold fish 25%, and 85,75 % in stripped catfish [10,11,12].…”
Section: Introduction mentioning
confidence: 99%
“…Recently, transgenesis development for aquatic animal is better to be transferred using electroporation method, because electroporation considered more suitable for the aquaculture and does not require special skills [8]. That is also seen in the efficacy of succesful gene transfer using sperm elctroporation method that has been reported to have higher efficiency compared with microinjection method, as shown in ayu fish (Plecogosus altivelis) the successful of gene transfer is 55%, in zebrafish and moad loach are 80%, in indian gold fish 25%, and 85,75 % in stripped catfish [10,11,12].…”
Section: Introduction mentioning
confidence: 99%
“…RAPD as dominant trait produced homozygotes as much as heterozygotes allele while the heterozygotes generated the polymorphic alleles (Liu, 2007). Buwono et al (2016) reported transgenic Mutiara catfish has success-Jurnal Biodjati 4(2):204-213, November 2019 http://journal.uinsgd.ac.id/index.php/biodjati fully inserted by CgGH that constructed from two GH gene derived from the fish own body (endogenous) and GH from outside the body (exogenous) thus effects of transgenic catfish revealed polymorphisms.…”
Section: Polymorphisms and Heterozygositymentioning
confidence: 99%
“…While on transgenesis fish, the stability of inheritance from excellent character (growth) is displayed on the F1 and F2 offspring, showing growth gene construct integrated into the fish's genome (Alimuddin et al, 2003;Rasal et al, 2016). Transgenesis application in Mutiara catfish using CgGH (Clarias gariepinus Growth Hormone), gene transfer (Buwono et al, 2016), and PhGH (Pangasius hypophthalmus Growth Hormone) gene transfer in African catfish (Dewi et al, 2013) were able to increase the catfish size two times larger than normal catfish.…”
mentioning
confidence: 99%
“…Next, it was pulsed with 30 volt electric level [8], pulse length was according to treatment and the pulse number was 4 times. Post electroporation, 275 physiological NaCL (total of 300 μL solution) was added into the sperm [9]. The following step was to observe the motility and viability of the post electroporation sperm.…”
Section: Electroporation Processmentioning
confidence: 99%